Using Gradebook in Blackboard - Parkes, Samantha (Issues in Language Instruction, 2018)
I do not use technology in my classes for technology’s sake. I am not that gifted with computers and some things that are intuitive to others are a mystery to me. However, if I think it will make my life easier and help me become a more transparent teacher, then I will do my best to figure out new programs and devices. This is how I came to use the Gradebook feature of Blackboard in my classes and why I believe it has not only helped me to adapt to the AEC’s grading system, but also has helped my students take a more active role in their own success in my courses.